Pemeriksaan Fisioterapi Gangguan Kognitif pada Lansia Dengan Mini Mental State Examination (MMSE) di Griya Lansia Husnul Khotimah Wajak - Dzikri Maulana Putra; Nungki Marlian Yuliadarwati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Cognitive impairment is one of the adverse effects for the elderly. Physiotherapy plays an important role in improving cognitive function in the elderly, namely by promotive, preventive, curative, and rehabilitative ways. Assessment of cognitive function with neuropsychological examination is the main key. A fairly popular cognitive function examination includes the Mini Mental State Examination (MMSE) Test. The method used was to provide counseling and examination related to cognitive impairment in the elderly using the MMSE (Mini Mental State Examination) questionnaire. Participants in counseling activities consisted of 30 elderly people. Before counseling the elderly are given questions (pre-test) about material about cognitive impairment. Furthermore, the elderly were given education related to cognitive impairment, then continued with a question and answer session, after that, the MMSE (Mini Mental State Examination) questionnaire was distributed. Pretest and posttest were conducted before and after counseling regarding the provision of cognitive function disorder material. Based on the data above, counseling activities carried out on understanding the elderly in the elderly griya husnul khotimah wajak related to the definition of cognitive function disorders, causes, signs and symptoms, and treatment, this is indicated by an increase in insight and knowledge of the elderly regarding cognitive function disorders in the elderly.